Water, sanitation and hygiene survey - Use of hydrogen sulfide strip at field level as a point-of-care test: A pilot study - P V Shilpa; Madhavi Bhargava (Wolters Kluwer Medknow Publications, 2018)
Safe drinking water is a basic element of primary health care. The government of India in its Indian Public Health Standards recommends the hydrogen sulfide (H2S) strip test as a desirable component at primary health centers for screening water for fecal coliforms. The objective of the present study was to conduct a water, sanitation and hygiene (WASH) survey followed by a H2S strip test of drinking water in a village with ninety households. The test was positive in 88% at the source and the point of consumption, with 100% concordance between both the points of test. A subsample of water samples was subjected to testing in microbiology laboratory, and fecal contamination was confirmed in all of them. To conclude, H2S strip test can be conveniently used at field level, and its ease of use and visual nature of results make it a useful point-of-care test of environmental and public health.